Migration, an alternative to bring resilience for coastal Bangladesh: Napitkhali Village experience - Mustari, Sohela; Karim, A.H.M Zehadul (European Journal of Social Sciences, 2017)
This article tries to show migration as an alternative, among many other alternatives, to establish resilience in a vulnerable coastal society of Bangladesh. This article thus highlights of social resilience in relation to the concept of migration that the coastal villagers conduct to bring stability in their social life. The research collected basic demographic data of the villagers of Napitkhali by using a simple survey. In addition, a total of 30 in-depth interviews with the villagers and professionals were conducted to have the depth information of the nature of migration and resiliency of the villagers. Apart from these, three Focus Group Discussions (FGDs) with the villagers also were conducted by the researcher(s) which undoubtedly establishes a link between migration and resilience. This article thus examines a few key points of migration in a coastal village of Bangladesh named Napitkhali of Satkhira district and finds that migration among the villagers mostly takes place seasonally for a temporary period. Moreover, mostly young male or the household head goes for migration to support their family. Finally, this article establishes that this migration is able to bring stability in their economic life which helps them to be resilient in their everyday life as well.